Effect Of Different Techniques Of Acidification By Sauerkraut Extracts To Physical Performance Of Acidified Fish Meal - B. Sulistiyanto; C.S. Utama; K. Nugoho (JURNAL KESEHATAN, 2009)
Abstract Research to obseme effect of diferent techniques o/ acidification by sauerkraut extracts to physicorganoleptically performance of acidified fish meal has been conducted in the Laboratory of Feed Technologt Faculty of Animal Science Diponegoro University. Extract of Sauerkraut is made by fermenting wastes of vegetable market (LPS) for 6 days, which is Etarting by molasses. Acidification of Wish by extract solution of LPS was conduct by dipping/or 0, 4 and 8 hours, and dippingfollowed by ensilingfor l0 days. Changes in pH, odor, color, texture and moisture content of acidified fish meal is parameters obsemed. Results of research indicate that the extract LPS can be used in the acidification of "Ikan rucah" by providing the value of pH j,4-4,9. Value of pH decreased with the soaking time, pH of fish in the form of post-acidification for 0, 4 and 8 hours, and soahngfollowed ensiling is 3,8; 4,0; 4.0 and 9.8. Acidified fish meal product of soaking 0 and 4 hours are characterized by typical smell ofextracl LPS, with a rather bright reddish color.  While soaking in 8 hours of extract of LPS provide typical smell of extract a bit Jlshy, with garnet color, and the Fish that was soakedfollowed by fermentationfor l0 days the smell is Fleshy fish with the color dark brown. The texture of the fish soaked Intact and slightly chewy, while the texture of fish that fermented to be soggt such as porridge. After drying the fish meal is made with lechniques of dipping smelly of fish meal and slightly sour smell, wilh light brown to brown color, while fish meal made withfermentation smell a bit rotten v,ith black brown color. Content of Moisture offish meal decreased in line with the time of soaking. It can be concluded that physical- organoleptically performance of Jish meal made with the dipping technique is better than that was made with ensiling. Keywords: acidifiedfish meal, dipping, ensiling, extracts Sauerkraut